La gestión de los grupos de interés: una reflexión sobre los desafíos a los que se enfrentan las empresas en la búsqueda de la sostenibilidad empresarial - Anna M. Gil Lafuente; Luciano B. Paula (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2011)
– The management of stakeholders is becoming increasingly important to the corporate sustainability. The engagement of stakeholders gives legitimacy to the company, generating trust and credibility. The enterprises that are seeking sustainability in their activities must know stakeholders, promote dialogue, meet the demands and expectations, and be transparent in the accountability for their actions. The sustainable company triggers continuous improvement and innovation and seeks for social acceptance to achieve success in their activities. In this context, our focus is on thinking about the main challenges faced by companies pursueing sustainable development through effective management of their stakeholders. We further propose the use of flexible tools that aid employers in decision making and help them improve the stakeholder management.
Keywords: M10; M14; 330; stakeholders; corporate sustainability; decision-making; fuzzy logic